Considerable humidity response of a well-aligned SOMS micro-wire flexible sensor by moisture-induced releasing of trapped electrons. Issue 33 (1st August 2017) - Chan, Kuei-Lin; Yang, Min-Han; Chiu, Hsin-Tien; Lee, Chi-Young
Abstract : Sandia Octahedral Molecular Sieves micro-wires (SOMS MWs) that exhibit ultra-high response to moisture and a short response time can be produced easily in an environmentally friendly mass production process. Abstract : Sandia Octahedral Molecular Sieves micro-wires (SOMS MWs) that exhibit ultra-high response to moisture and a short response time can be produced easily in an environmentally friendly mass production process. They are excellent candidate materials for use in humidity sensors. SOMS MWs were synthesized using niobium pentoxide as a precursor in concentrated sodium hydroxide solution. To fabricate humidity-sensing devices, electrophoresis was utilized to align the SOMS MWs on a polyethylene terephthalate (PET) substrate. The degree of alignment of SOMS MWs can be tuned by controlling the electric field during electrophoresis. Both well-aligned SOMS MWs (S-1.00) and randomly distributed SOMS MWs (S-0.00) exhibit maximum sensitivities to humidity ( R RH / R DRY ) of almost 10 4 and 10 7 respectively, and both exhibit short response times (34 and 38 s) and recovery times (7 and 10 s); these MWs outperform metal oxide ceramic-based materials in sensing humidity. Furthermore, the humidity response of S-1.00 exceeds that of S-0.00 by three orders of magnitude, and this result cannot be explained with reference to the Grotthuss mechanism. Therefore, the moisture-induced carriers from trapped electrons contribute significantly to the humidity response of SOMS MWs. In addition, with outstanding humidity sensing-performance under extreme bending conditions and superior durability after being bent hundreds of times, the well-aligned SOMS MW sensor is a favorable candidate for emerging multifunctional electronic-skin.